2018
DOI: 10.18203/2349-3291.ijcp20181508
|View full text |Cite
|
Sign up to set email alerts
|

Composite index of anthropometric failure among under 5 children attending the Immunoprophylaxis clinic in a tertiary care hospital in Nagpur, Maharashtra, India

Abstract: Background: Under nutrition is a global public health problem. There are numerous methods of assessment of malnutrition among which CIAF is the most recent, relatively robust since it envisages all the parameters for estimation of nutritional status of the children. So, this study was conducted to find the rates of composite index of anthropometric failure in the children attending the Immunoprophylaxis clinic in a tertiary care hospital of Nagpur and to find associations with the socio demographic variables.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(29 reference statements)
2
2
0
1
Order By: Relevance
“…In the same year, Kherde et al conducted a study in Nagpur, India. The CIAF incidence in the region is almost the same as the results of this study which is 23.26% [14] [15] The number of short -thin children in cities or villages shows that nutritional problems that occur are complex and acute -chronic. The unique problematic condition is found in many children who have highly educated mothers and are not economically productive (more at home).…”
Section: Discussionsupporting
confidence: 77%
“…In the same year, Kherde et al conducted a study in Nagpur, India. The CIAF incidence in the region is almost the same as the results of this study which is 23.26% [14] [15] The number of short -thin children in cities or villages shows that nutritional problems that occur are complex and acute -chronic. The unique problematic condition is found in many children who have highly educated mothers and are not economically productive (more at home).…”
Section: Discussionsupporting
confidence: 77%
“…Their study observed that as anthropometric failure incidence increases, the effect of socio-economic and demographic factors on undernutrition also increases and highlights the use of CIAF by health workers. Similar results by constructing the CIAF were found among preschool children of Chapra in Nadia district of West Bengal (Biswas et al, 2009), among children between two years and six years from Bauri caste in West Bengal (Das & Bose, 2009), and while studying childhood morbidities in rural Wardha in Maharashtra (Deshmukh et al, 2009; for regional studies, see also Boregowda et al, 2015; Dewan et al, 2015; Dhok & Thakre, 2016; Gupta et al, 2017; Kherde et al, 2018; Patsa & Banerjee, 2018; Savanur & Ghugre, 2015).…”
Section: Review Of Literaturesupporting
confidence: 54%
“…Seven categories propose a supplementary measure to assess the undernutrition and estimate the prevalence of stunting, wasting and underweight in separate measures (Nandy et al 2005;Dewan et al 2015;Dhok and Thakre 2016;Ziba et al 2018). Several researchers have reported the immensity of child undernutrition using CIAF among Indian children (Nandy et al 2005;Seetharaman et al 2007;Mandal and Bose 2009;Sen and Mondal 2012;Boregowda et al 2015;Dewan et al 2015;Savanur and Ghugre 2015;Dhok and Thakre 2016;Gupta et al 2017;Vollmer et al 2017;Kherde et al 2018;Patsa and Banerjee 2018).…”
Section: Introductionmentioning
confidence: 99%